Everyday and family contexts of youth computer cultures - Oblak, Tanja (Annales. Series historia et sociologia, 2014)
In this paper we aimed to analyse the ways in which everyday context and family climate determine the complex structure of youth computer cultures, particularly the patterns that young people use in relation to computer activities and their place within the youth life. A representative quantitative survey among Slovenian youngsters aged 15-24, still living with their parents and going to school, revealed three different types of youth computer culture: The strongest factor predicting the passive, TV-like entertainment computer culture is the outgoing and entertaining free time pattern; the active and informative computer use is the most strongly positively predicted by the culturally engaged free-time pattern; the interactive and socially oriented computer culture is predicted only by the outgoing and entertaining free time pattern. The analysis also showed that the quality of the relationship between parents and children as perceived by the youngsters has no effect on youth computer culture within our sample.
Keywords: Družina; Family; Informacijska tehnologija; Information technology; Leisure; Mladina; Prosti čas; Slovenia; Slovenija; vsakdanje življenje; Youth